ภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษาที่ส่งผลต่อองค์การสมรรถนะสูง ของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร - เกื้ออนันต์, ดารารัตน์; ศิริสุขศิลป์, เสาวนี (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2024)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาความสัมพันธ์ระหว่างภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษากับความเป็นองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร 2) ศึกษาภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษาที่ส่งผลต่อองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร และ 3) เพื่อศึกษาแนวทางการพัฒนาภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษาที่ส่งผลต่อองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร มีการดำเนินการวิจัย 2 ระยะ ระยะที่ 1 ศึกษาความสัมพันธ์ระหว่างภาวะผู้นำเหนือผู้นำกับความเป็นองค์การสมรรถนสูง ด้วยการหาค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน และศึกษาภาวะผู้นำเหนือผู้นำที่ส่งผลต่อองค์การสมรรถนะสูงของสถานศึกษา ด้วยการวิเคราะห์การถดถอยพหุคูณ (Multiple Regression Analysis) กลุ่มตัวอย่าง คือ ผู้บริหารและครู จำนวน 269 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามมาตราส่วนประมาณค่า 5 ระดับ มีค่าความเชื่อมั่น 0.98 ระยะที่ 2 ศึกษาแนวทางในการพัฒนาภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษา ด้วยวิธีการสัมภาษณ์เชิงลึก (In-Depth Interview) จากทรงคุณวุฒิ จำนวน 3 คน            ผลการวิจัยพบว่า 1) ภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษาทุกด้านมีความสัมพันธ์ในทางบวกกับองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร อย่างมีนัยสำคัญที่ระดับ .01 โดยมีค่าสัมประสิทธิ์สหสัมพันธ์มากที่สุด คือ ด้านการเป็นแบบอย่างของผู้นำตนเอง และน้อยที่สุดคือ   ด้านการสร้างภาวะผู้นำตนเอง 2) ภาวะผู้นำเหนือผู้นำของผู้บริหารสถานศึกษาที่ส่งผลต่อองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร ได้แก่ การเป็นแบบอย่างของผู้นำตนเอง (X 2 )  การเสริมแรงอย่างสร้างสรรค์ (X 4 ) และการสร้างพลังเชิงบวก (X 3 ) 3) แนวทางการพัฒนาภาวะผู้นำเหนือผู้นำที่ส่งผลต่อองค์การสมรรถนะสูงของสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษามุกดาหาร ด้านการเป็นแบบอย่างของผู้นำตนเอง ปฏิบัติตนเป็นแบบอย่างที่ดี ทั้งในการในปฏิบัติงาน และการปฏิบัติตน ให้เป็นที่ยอมรับในสถานศึกษา ด้านการพัฒนาการเสริมแรงอย่างสร้างสรรค์ ได้แก่ สนับสนุนให้บุคลากรค้นพบศักยภาพ ปฏิบัติงานให้ตรงตามสายงานและความถนัด และกำหนดเกณฑ์การประเมินผลการปฏิบัติงานและชี้แจงแก่บุคลากรอย่างชัดเจน และเสนอแนะให้แก้ไขสิ่งที่ผิดพลาดด้วยความเป็นกัลยาณมิตร ด้านการพัฒนาการสร้างพลังเชิงบวก ส่งเสริมให้บุคลากรมีส่วนร่วมในการกำหนดจุดมุ่งหมาย และแนวทางในการปฏิบัติงาน โดยจัดให้มีการระดมความคิด และแสดงความคิดเห็นร่วมกันอย่างสร้างสรรค์             The objectives of this research were: 1) to study the relationship between super leadership for school administrator and high performance organization of schools under the office of Mukdahan Secondary Educational Service Area Office 2) to study super leadership for school administrator affecting high-performance organizations of schools under the office of Mukdahan Secondary Educational Service Area and 3) to study the way to develop super leadership for school administrator affecting high-performance organizations of schools under the office of Mukdahan Secondary Educational Service Area. There are 2 phases of research. Phase 1: Studying the relationship between super leadership for school administrator and high-performance organization by using Pearson product moment coefficient and studying the effect of super leadership on high-performance organizations of schools by using multiple regression analysis. The samples were administrators and teachers total 269 persons. The research tool was a 5-point estimation scale questionnaire with a reliability of 0.98. Phase 2: Studying the approach to develop super leadership for school administrators by using in-depth interview from 3 qualified persons.            The research findings were as follows: 1. Super leaders for school administrator in all aspects had a positive correlation with high-performance organizations of schools under the office of Mukdahan Secondary Education Service Area significantly at the .01 level, with the “Highest” correlation was the aspect of being a role model for self-leadership and the “Lowest” correlation was the building of self-leadership. 2. Super leadership for school administrator affecting high-performance organizations of schools under the office of Mukdahan Secondary Educational Service Area, including being a role model of self-leadership (X 2 ), creative reinforcement (X 4 ), and creating positive energy (X 3 ). 3. The development approaches of super leadership affecting high-performance organizations guidelines of educational institutions under the office of Mukdahan Secondary Educational Service Area. Self-leadership role model as behaving as a good role model both in work and behaving in order to be accepted in educational institutions. Development of creative reinforcement, including encouraging personnel to discover their potential, performing the duties according to the line of work and expertise, and setting criteria for performance evaluation and clarification to personnel as well as suggestions for correcting any mistakes with be an ally. Developing positive energy: encouraging personnel to participate in setting goals and guidelines for work by organizing brainstorming and expressing ideas together creatively.